Organizational risk using network analysis - Armstrong, Helen; McCulloh, I. (Centre for Security, Communications & Network Research, 2010)
Business organizations are held together not only by formal reporting and authority networks but also by informal networks that connect people across numerous layers of hierarchical organizational structures. People form networks of contacts and communications and through these networks they 'get things done'. Although extensive research has been carried out on social networks the application of these methods to organizational risk has not been widely published. However, network analysis does provide a source of information on potential risks to aid decision-makers within an organization. The application of network analyses in identifying and measuring potential risks based upon the analyses of people, knowledge, tasks and resources is presented in this paper.